Acute effects of air pollution on respiratory disease mortalities and outpatients in Southeastern China - Zhe Mo (Nature Portfolio, 2018)
Abstract The objective of this study was to investigate the potential association between air pollutants and respiratory diseases (RDs). Generalized additive models were used to analyze the effect of air pollutants on mortalities or outpatient visits. The average concentrations of air pollutants in Hangzhou (HZ) were 1.6–2.8 times higher than those in Zhoushan (ZS), except for O3. In a single pollutant model, the increased concentrations of PM2.5, NO2, and SO2 were strongly associated with deaths caused by RD in HZ, while PM2.5 and O3 were associated with deaths caused by RD in ZS. All air pollutants (PM2.5, NO2, SO2, and O3) were strongly associated with outpatient visits for RD in both HZ and ZS. In multiple pollutant models, a significant association was only observed between PM2.5 and the mortality rate of RD patients in both HZ and in ZS. Moreover, strong associations between SO2, NO2, and outpatient visits for RD were observed in HZ and ZS. This study has provided evidence that both the mortality rates and outpatient visits for RD were significantly associated with air pollutants. Furthermore, the results showed that different air pollutant levels lead to regional differences between mortality rates and outpatient visits.